Does "biological quantum entanglement" exists? - Djuro Koruga; Jadran Bandić; Lidija Matija; Spomenko Mihajlović; Igor Koruga; Nikola Ilanković (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
In literature and clinical reports connections between a heart condition (blood properties) and emotional and mental states are documented [1,2]. It is well known that psychosocial risk factors may lead to the activation of mechanisms responsible for somatic dysfunction of the cardiovascular system.